2008
DOI: 10.1016/j.jcf.2008.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Lipoxin A4 and interleukin-8 levels in cystic fibrosis sputum after antibiotherapy

Abstract: As previously reported, after antibiotics therapy, FEV(1) and FVC significantly improved. While neutrophil cell counts and IL-8 levels decreased, the LXA(4) levels significantly increased after antibiotics therapy and were inversely correlated with IL-8 levels. In conclusion, we reported a correlation between antibiotics treatments and inflammatory markers in CF sputum. Our data provide evidences for a novel effect of antibiotics increasing the concentration of the anti-inflammatory lipid mediator LXA(4).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…Consistent with the notion that P. aeruginosa actively manipulates the inflammatory environment in the airway, other studies have demonstrated that i.v. antibiotic treatments increase LXA 4 levels, while decreasing proinflammatory chemokine concentrations in BALF of patients with CF (28). As a result, P. aeruginosa may be uniquely poised to exploit both pro-and antiinflammatory strategies to thwart host defense mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the notion that P. aeruginosa actively manipulates the inflammatory environment in the airway, other studies have demonstrated that i.v. antibiotic treatments increase LXA 4 levels, while decreasing proinflammatory chemokine concentrations in BALF of patients with CF (28). As a result, P. aeruginosa may be uniquely poised to exploit both pro-and antiinflammatory strategies to thwart host defense mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In order to test the hypothesis that eicosanoid class switching is defective in CF, giving rise to a failure to resolve acute inflammation, we compared eicosanoids temporally associated with the ''switch'' from propagation to resolution, LTB 4 and LXA 4 , respectively. In addition, with the expectation that the phase of inflammation would be affected by the infectious context [29], we conducted subgroup analysis based on the presence or absence of microbial pathogens detected in the BAL fluid. By comparing relative mediator concentrations, expressed as a LXA 4 /LTB 4 ratio, we demonstrate that the balance in eicosanoid biosynthesis weighs heavily in favour of LXA 4 production over LTB 4 production in control BAL when compared to CF BAL ( fig.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that markers of inflammation are elevated in the sputum of individuals with CF, including neutrophil elastase and IL-8 (2, 3); while markers of inflammation resolution, such as lipoxin A4, are decreased (4). Individuals with CF also display abnormalities of fatty acid (FA) metabolism, most notably characterized by decreased linoleic acid (LA) and docosahexaenoic acid (DHA) levels (5, 6).…”
Section: Introductionmentioning
confidence: 99%